Association of Mycoplasma genitalium with balanoposthitis in men with non-gonococcal urethritis. Issue 1 (18th September 2010) - Horner, Patrick J; Taylor-Robinson, David
Abstract : Objective: To determine whether Mycoplasma genitalium is associated with balanitis and/or posthitis in a previous study of the role of M genitalium in men with acute non-gonococcal urethritis (NGU). Methods: In a previous study of men with acute NGU, the existence of balanitis and/or posthitis was recorded. Chlamydia trachomatis, M genitalium and ureaplasmas were sought in urethral swabs and urine using a direct fluorescent antibody test and in-house PCR, an in-house PCR and a culture method, respectively. Men were treated with doxycycline or erythromycin. Results: M genitalium was associated significantly (p=0.01) with balanitis and/or posthitis in 114 men with acute NGU. This association persisted when there was control for C trachoma tis and urethral discharge (p=0.021, OR 4.1, 95% CI 1.2 to 13.5). C trachomatis and ureaplasmas were not associated with balanitis and/or posthitis. Conclusion: Detection of M genitalium in men with acute NGU was associated significantly with balanitis and/or posthitis. The association is biologically plausible and may have a role in HIV-1 transmission and susceptibility.